1975
DOI: 10.1145/1041707.1041709
|View full text |Cite
|
Sign up to set email alerts
|

Issues in computer performance evaluation

Abstract: This paper summarizes the results of an ACM/NBS Workshop on Computer Performance Evaluation. Computer Performance Evaluation (CPE) was selected as the subject of an ACM/NBS Workshop because of the significant leverage CPE activities can have on computer usage. This paper describes a number of conclusions abstracted from the discussions as well as presenting recommendations formally adopted by the participants. While several of these conclusions indicate that improvements are needed in performance analysis tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…1977;Shannon and Weaver, 1949;Sprague and Carlson, 1982]. Boehm and Bell [1977] concluded that both the cost of a system and the information needs of the users must be considered in any information systems evaluation. This idea was later discussed and supported by Chandler [1982] who favored a multiple criteria approach.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…1977;Shannon and Weaver, 1949;Sprague and Carlson, 1982]. Boehm and Bell [1977] concluded that both the cost of a system and the information needs of the users must be considered in any information systems evaluation. This idea was later discussed and supported by Chandler [1982] who favored a multiple criteria approach.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…In the computer system domain, performance is measured in terms of resource utilization, cost, and efficiency while in the user domain, throughput, reliability, and response time are common measures. A workshop sponsored by ACM and NBS [1] concluded that any performance analyses "should recognize both the costs of a computer installation and the needs of users for service. "…”
Section: Introductionmentioning
confidence: 99%